2016
DOI: 10.1016/j.jmatprotec.2015.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing at double the speed

Abstract: The speed of manufacturing processes today depends on a trade-off between the physical processes of production, the wider system that allows these processes to operate and the co-ordination of a supply chain in the pursuit of meeting customer needs. Could the speed of this activity be doubled? This paper explores this hypothetical question, starting with examination of a diverse set of case studies spanning the activities of manufacturing. This reveals that the constraints on increasing manufacturing speed hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 114 publications
0
16
0
Order By: Relevance
“…This behavior can be explained by the effect of a heating rate and holding time on the nucleation and growth of austenite and the dissolution of Fe 3 C carbides. Several studies [12][13][14] have indicated that during rapid reheating the classical view of phase transformations will deviate markedly from those observed during equilibrium conditions. That is, the kinetics of transformation will have a different behavior.…”
Section: Effect Of Heating Rate On Transformation Temperatures (A C1 mentioning
confidence: 99%
“…This behavior can be explained by the effect of a heating rate and holding time on the nucleation and growth of austenite and the dissolution of Fe 3 C carbides. Several studies [12][13][14] have indicated that during rapid reheating the classical view of phase transformations will deviate markedly from those observed during equilibrium conditions. That is, the kinetics of transformation will have a different behavior.…”
Section: Effect Of Heating Rate On Transformation Temperatures (A C1 mentioning
confidence: 99%
“…However, pushing cutting conditions boundaries in machining titanium is required for faster manufacturing [4]. Owing to low thermal conductivity such as 7.3 W/m·K for annealed Ti-6Al-4V, cutting titanium generates a large amount of heat close to the machining zone.…”
Section: Introductionmentioning
confidence: 99%
“…Mechatronics components are often substituted in case of damage. A potential future technology for spare part production is Additive Layer Manufacturing that allows producing directly from 3D scan data [3,47,103]. The mechanism involves cleaning the damaged area, depositing new material ( Fig.…”
Section: Repair Mechanismsmentioning
confidence: 99%